2023
DOI: 10.21323/2618-9771-2022-5-4-376-382
|View full text |Cite
|
Sign up to set email alerts
|

Studying an effect of thermal treatment methods on physico-chemical properties of beef depending on aging technology

Abstract: Modern methods for aging and thermal treatment facilitate an improvement in beef sensory properties. The aim of the research was to study an effect of different types of thermal treatment on quality of steaks from dry-aged beef. Steaks were obtained from the rib cut from carcasses of grain-fed young bulls; aging duration was 35 days (temperature 0–1 ºС, air relative humidity 74–75%). Aging duration in the control sample was five days (temperature 0–4 ºС, air relative humidity 80–85%). The methods for thermal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Previous studies showed influences of visual marbling score, carcass weight, cooking methods, aging technologies, etc. on the sensory quality and consumer's acceptance of fresh meat (Cannata et al, 2010;Gurinovich et al, 2023;Hwang et al, 2019;Hwang et al, 2020). To our knowledge, there are a limited number of studies that have examined the effect of cooking methods on fresh meat quality, especially beef (Grujić et al, 2014;Wołoszyn et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed influences of visual marbling score, carcass weight, cooking methods, aging technologies, etc. on the sensory quality and consumer's acceptance of fresh meat (Cannata et al, 2010;Gurinovich et al, 2023;Hwang et al, 2019;Hwang et al, 2020). To our knowledge, there are a limited number of studies that have examined the effect of cooking methods on fresh meat quality, especially beef (Grujić et al, 2014;Wołoszyn et al, 2020).…”
Section: Introductionmentioning
confidence: 99%